PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PT. SUKSES ABADI INDONESIA NGANJUK - Bayu Setya Budi; Faris Fadhilah Zakiy; Atha Ardhana; Ilham Helmy Firdaus; Muhammad Hakim Ashabi (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of job satisfaction and organizational commitment on the manifestation of Organizational Citizenship Behavior (OCB) at PT. Sukses Abadi Indonesia Nganjuk. In the context of increasingly intense business competition, organizations are not only required to achieve financial targets but also to establish a work environment that supports employee well-being. Job satisfaction, representing individuals' positive perceptions of various aspects of their work, and organizational commitment, reflecting employees' loyalty to the organization's vision and values, play a strategic role in encouraging proactive employee behaviors that contribute to organizational performance. The findings of this study reveal that job satisfaction and organizational commitment have a statistically significant influence on the tendency to exhibit OCB. Employees who feel satisfied and emotionally attached to the organization demonstrate a higher willingness to contribute beyond their formal roles to support the achievement of organizational goals.